Odpowiedź :
1.Zapisz w jak naprostrzej postaci:
a) x(5x-2)-2x(x+1)
5x^-2x-2x^-2x=3x^-4x
b)(a+2)^(kwadratu)-(a-2)^(kwadratu)
a^+2*a*2+2^-(a^-2*a*2+2^)=a^+4a+4-a^+4a-4=8a
2.wylacz wspolny czynnik przed nawias
a) xy+y=y(x+y)
b) 2x^(kwadrat)+4x=2x(x+2)
c)9ab^(kwadrat)+6b^a=3ab(3b+2b)
a) x(5x-2)-2x(x+1)
5x^-2x-2x^-2x=3x^-4x
b)(a+2)^(kwadratu)-(a-2)^(kwadratu)
a^+2*a*2+2^-(a^-2*a*2+2^)=a^+4a+4-a^+4a-4=8a
2.wylacz wspolny czynnik przed nawias
a) xy+y=y(x+y)
b) 2x^(kwadrat)+4x=2x(x+2)
c)9ab^(kwadrat)+6b^a=3ab(3b+2b)
a) =5x^(kwadrat)-2x-2x^(kwadrat)-2x=3x^(kwadrat)-4x
b) =(a+2)(a+2)-(a-2)(a-2)=a^(kwadrat)+2a+2a+4-a^(kwadrat)+2a+2a-4=a^(kwadrat)+4a+4-a^(kwadrat)+4a-4=8a
c) =2a^(kwadrat)-ab+4ba-2b^(kwadrat)-3ab=2a^(kwadrat)-6ab-2b^(kwadrat)
a) =y(x+1)
b) =2x(x+2)
c) =3(3ab^(kwadrat) +2b^(kwadrat)a)
a)delta=36-4*1*9=36-36=0
x1= -3
x2= -3
b)
b) =(a+2)(a+2)-(a-2)(a-2)=a^(kwadrat)+2a+2a+4-a^(kwadrat)+2a+2a-4=a^(kwadrat)+4a+4-a^(kwadrat)+4a-4=8a
c) =2a^(kwadrat)-ab+4ba-2b^(kwadrat)-3ab=2a^(kwadrat)-6ab-2b^(kwadrat)
a) =y(x+1)
b) =2x(x+2)
c) =3(3ab^(kwadrat) +2b^(kwadrat)a)
a)delta=36-4*1*9=36-36=0
x1= -3
x2= -3
b)